1993
DOI: 10.1063/1.109292
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear interdiffusion in semiconductor superlattices: Case of CdTe/HgTe

Abstract: Experiments have been designed to measure the interdiffusion coefficients in CdTe/HgTe (001) superlattices grown by molecular beam epitaxy. The interdiffusion coefficients are deduced from double-crystal x-ray diffraction on samples annealed in the 200–240 °C range under a Hg saturated pressure. Our results indicate that the interdiffusion is strongly dependent on concentration with a coefficient given by D(CCd,T)=1.0 exp{[−1.45(±0.1) eV]/(kT)} exp {[−0.55 (±0.1) CCd eV]/(kT)} cm2/s. The activation energies ΔE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…This value is consistent with the extrapolation of Tardot et al [13] for growth at 180 1C and has to be considered as a maximum value for interdiffusion in our structures assuming our maximal growth temperature is 10 1C lower.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…This value is consistent with the extrapolation of Tardot et al [13] for growth at 180 1C and has to be considered as a maximum value for interdiffusion in our structures assuming our maximal growth temperature is 10 1C lower.…”
Section: Discussionsupporting
confidence: 64%
“…As far as we know, interdiffusion characteristics were only determined after few hours of annealing at temperatures ranging from 110 1C [11] to more than 450 1C [12] under Hg saturated vapour pressure. One of these studies led by Tardot et al [13] demonstrated diffusion coefficients of 2 Â 10 À 16 cm²/s for Cd in HgTe in the case of superlattices annealed at 200 1C. Indeed the diffusion process between these two materials is characterized by the important diffusion of Cd into HgTe layer creating a HgCdTe intermixing layer at the interface.…”
Section: Hgte/cdte Interface Characterizationsmentioning
confidence: 96%
“…15,16 Nonlinear thermal diffusion, i.e., an interdiffusion coefficient which depends on the composition of the alloy, has been used in cases where the two compounds exhibit very different properties, such as at the CdTe-HgTe interface where diffusion coefficients in HgTe are larger than in CdTe by several orders of magnitudes. 17,18 In other structures involving CdTe and another telluride, such as ZnTe, 19 MnTe 20,21 or MgTe, 20,21 any deviation from linear interdiffusion would be much more difficult to put into evidence, and the simple Fick's law was used to describe thermal interdiffusion. The present case is even more complicated, since the barrier is a pseudoternary alloy, Cd 1ϪxϪy Zn x Mg y Te, so that coupled equations governing the interdiffusion of Cd, Mg, and Zn should be considered and solved to give three concentration profiles with C Mg (z)ϩC Cd (z)ϩC Zn (z)ϭ1 at any position.…”
Section: Interdiffusion Studymentioning
confidence: 99%
“…Although many values have been published for the diffusion coefficients, we referred to the set of values in the report ofa HgCdTe simulator5 The values ofD s and the composition dependence of the vacancy diffusion are given by Tardot et al 6 The coefficients and the constants were therefore set to be,…”
Section: Viv+ Lsmentioning
confidence: 99%